PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, LIKUIDITAS, LEVERAGE TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN - , FAYLASUFAH (Jurnal Akuntansi AKUNESA, 2017)
Characteristics of financial statements are very important for investors in decision making. Timeliness of financial statement submission is one type of characteristics of financial statements, but there are still many companies that make the delivery of financial statements beyond the specified time limit. This research aims to determine the variables that affect the timeliness of the delivery of financial statements, so the company does not make delays in delivering financial statements. The sample in this research are all companies in the mining sector in Indonesia Stock Exchange that registered in 2014-2016. Hypothesis testing in this research is analyze by logistic regression analysis. The results showed that firm size and profitability variables did not affect the timeliness of financial reporting, while liquidity and leverage variables affect the timeliness of financial statement